Good neighbors or good prisoners? Non-uniformed staff beliefs about incarcerated people influence prison social climate. (April 2023) - Gonzales, Carlos M; Dewey, Susan; Anasti, Theresa; Lockwood-Roberts, Susan; Codallos, Kym; Gilmer, Brittany; Dolliver, Matthew
We analyzed results from semi-structured interviews and participant observation with educators, clinical staff, and administrators who worked at nearly 100 different correctional facilities centrally managed by eight separate state prison systems to understand how the beliefs they hold about the life experiences and future trajectories of incarcerated people influence prison social climate. We found that staff who regard incarcerated people as past and/or future neighbors are more likely to foster a safe, mutually respectful prison social climate conducive to positive personal transformation. Envisioning prison social climate as a product of the relationship between staff and incarcerated people demonstrates how prisons and communities interact with each other to shape the past and future possibilities for people who are incarcerated. Our results offer six policy implications, to (1) mandate administrative-institutional commitment to creating a positive prison social climate in which correctional staff and incarcerated people are partners in rehabilitation; (2) expand existing program opportunities in prison to ensure widespread availability of educational, vocational, and therapeutic treatment programs; (3) increase representation of staff who share experiential and demographic characteristics with incarcerated people to reduce or eliminate unconscious bias; (4) generate public awareness of, and support for, rehabilitative measures proven to better prepare incarcerated people for release from prison; (5) increase community engagement by publicizing graduation and other positive events; and (6) foster a mutually supportive work environment among educational, clinical, and administrative staff.